Cotrimoxazole prophylaxis and risk of severe anemia or severe neutropenia in HAART-exposed, HIV-uninfected infants. - Scott Dryden-Peterson; Oluwemimo Jayeoba; Michael D Hughes; Haruna Jibril; Kenneth McIntosh; Taolo A Modise; Aida Asmelash; Kathleen M Powis; Max Essex; Roger L Shapiro; Shahin Lockman (PLoS ONE, 2013)
Prophylactic cotrimoxazole is recommended for infants born to HIV-infected mothers. However, cotrimoxazole may increase the risk of severe anemia or neutropenia.We compared the proportion of HIV-exposed uninfected (HIV-EU) infants experiencing incident severe anemia (and separately, severe neutropenia) between a prospective cohort receiving prophylactic cotrimoxazole from 1 to 6 months vs. infants from two prior trials who did not receive cotrimoxazole. Infants were from rural and urban communities in southern Botswana.A total of 1705 HIV-EU infants were included. Among these 645 (37.8%) were fed with iron-supplemented formula from birth. Severe anemia developed in 87 (5.1%) infants, and severe neutropenia in 164 (9.6%) infants. In an analysis stratified by infant feeding method, there were no significant differences in the risk of severe anemia by prophylactic cotrimoxazole exposure-risk difference, -0.69% (95% confidence interval [CI] -2.1 to 0.76%). Findings were similar in multivariable analysis, adjusted odds ratio (aOR) 0.35 (95% CI 0.07 to 1.65). There were also no significant differences observed for severe neutropenia by cotrimoxazole exposure, risk difference 2.0% (95% CI -1.3 to 5.2%) and aOR 0.80 (95% CI 0.33 to 1.93).Severe anemia and severe neutropenia were infrequent among HIV-exposed uninfected infants receiving cotrimoxazole from 1-6 months of age. Concerns regarding hematologic toxicity should not limit the use of prophylactic cotrimoxazole in HIV-exposed uninfected infants. CLINICALTRIAL.SGOV REGISTRATION NUMBERS: NCT01086878 (http://clinicaltrials.gov/show/NCT01086878), NCT00197587 (http://clinicaltrials.gov/show/NCT00197587), and NCT00270296 (http://clinicaltrials.gov/show/NCT00270296).